The Idea of Islamic Ecotheology in Responding to the Global Environmental Crisis: An Analysis of the Concepts of Khalifah, Mīzān, and Maṣlaḥah - Maulana Bagus Rahmat; Masruchin; Fauzan (Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract : The global ecological crisis has become a real threat due to the unsustainable exploitation of natural resources. This study aims to explore the contribution of Islamic theology in shaping ecological awareness through the concepts of khalifah (stewardship), mīzān (balance), and maṣlaḥah (public interest). The method used is a literature study with a qualitative approach to Qur’anic verses and scientific interpretations. Based on the results, Islam is a religion of Rahmatan lil ‘Alamin (mercy to all creation) which teaches balance and forbids all forms of environmental destruction. These teachings are highly relevant in addressing the challenges of today's ecological crisis. Therefore, a theological approach based on Islamic values can be an important alternative in efforts to overcome environmental damage caused by anthropocentric paradigms and modern exploitation. Keywords : Ecology; Islamic Ecoteology; Khalifah; Maṣlaḥah; Mīzān. Abstrak : Krisis ekologi global telah menjadi ancaman nyata akibat eksploitasi sumber daya alam yang tidak berkelanjutan. Penelitian ini bertujuan mengkaji kontribusi teologi Islam dalam membentuk kesadaran ekologis melalui pendekatan konsep khalifah, mizan, dan maṣlaḥah. Metodologi yang digunakan adalah kajian pustaka dengan pendekatan kualitatif terhadap ayat-ayat Al-Qur'an dan tafsir-tafsir ilmiah. Berdasarkan hasil penelitian, Islam adalah agama yang Rahmatan lil 'alamin. mengajarkan keseimbangan dan larangan terhadap segala bentuk kerusakan lingkungan. Ajaran ini sangat relevan dalam menanggapi tantangan krisis ekologi masa kini. Oleh karena itu, pendekatan teologis berbasis nilai Islam dapat menjadi alternatif penting dalam upaya mengatasi kerusakan lingkungan yang disebabkan oleh paradigma antroposentris dan eksploitasi modern. Kata kunci : Ekologi; Ekoteologi Islam; Khalifah; Maṣlaḥah; Mīzān